Tanggung jawab Pemuda dalam Islam: Studi Takhrij dan Syarah Hadis - Luthfi Miftahul Anwar (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the responsibility of youth. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the responsibility of youth in Imam Abu Daud's narration No. 3875. The results and discussion of this research show that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Imam Abu Daud No. 3875 is relevant to be used as an Islamic foundation on the responsibility of youth in religious and social life.